2022
DOI: 10.1155/2022/5410377
|View full text |Cite
|
Sign up to set email alerts
|

Orcinol Glucoside Improves Senile Osteoporosis through Attenuating Oxidative Stress and Autophagy of Osteoclast via Activating Nrf2/Keap1 and mTOR Signaling Pathway

Abstract: Oxidative stress and autophagy play essential roles in the development of senile osteoporosis which is characterized by disrupted osteoclastic bone resorption and osteoblastic bone formation. Orcinol glucoside (OG), a phenolic glycoside isolated from Curculigo orchioides Gaertn, possesses antiosteoporotic properties. This study examined the protective effects of OG on bone loss in SAMP6 mice and explored the underlying mechanisms. The osteoporotic SAMP6 mice were treated with OG oral administration. RAW264.7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…In addition, p70S6K has been identified as an inhibitor for autophagy, working downstream of the mTORC1 complex. Activation of the mTOR‐p70S6K signaling pathway by orcinol glucoside suppresses autophagy and osteoclast differentiation (Gong et al., 2022 ).…”
Section: How Do Hallmarks Of Aging Participate In the Pathogenesis Of...mentioning
confidence: 99%
“…In addition, p70S6K has been identified as an inhibitor for autophagy, working downstream of the mTORC1 complex. Activation of the mTOR‐p70S6K signaling pathway by orcinol glucoside suppresses autophagy and osteoclast differentiation (Gong et al., 2022 ).…”
Section: How Do Hallmarks Of Aging Participate In the Pathogenesis Of...mentioning
confidence: 99%
“…These two activated pathways synergistically facilitated the osteogenic progress. In terms of the autophagy of osteoclasts, Wan Gong et al employed a phenolic glycoside named orcinol glucoside (OG) to increase the production of Nrf-2 in osteoclast precursors to phosphorylate the mTOR signaling, resulting in the blockage of ROS-induced autophagy [ 69 ]. Another study regarding three phenolic acids (tannic acid (TA), gallic acid (GA) and ellagic acid) also confirmed their negative effects on the autophagy of osteoclasts via decreasing ROS, intracellular Ca 2+ content and mitochondrial membrane potentials [ 70 ].…”
Section: Phenolic Compounds Regulate Btcsmentioning
confidence: 99%
“… 156 Orcinol glucoside (OG), a naturally occurring phenolic glycoside derived from Curculigo curculigo, exhibits a multitude of beneficial properties, including antioxidative, anxiolytic, neuroprotective, and anti-osteoporotic activities. 157 , 158 Senile OP is associated with oxidative stress, Gong et al have reported that OG holds the potential to mitigate oxidative stress and curb OCs autophagy by activating the Nrf2/Keap1 and mTOR signaling pathways. Additionally, OG exerts a down-regulatory effect on OCs differentiation and function, thereby presenting a preventive approach against senile OP.…”
Section: Natural Compounds Regulate Obs and Ocs Autophagy Signaling P...mentioning
confidence: 99%
“…Additionally, OG exerts a down-regulatory effect on OCs differentiation and function, thereby presenting a preventive approach against senile OP. 158 Lycorine is an alkaloid isolated from Lycoraceae plants, which has anti-inflammatory and antioxidant effects. 159 Notably, lycorine exhibits the ability to diminish the production of mROS, modulate the triggering signal for autophagy via the mROS/TRPML1/TFEB axis, and mitigate lipopolysaccharide-induced OCs autophagy, as well as suppress OCs activity and abundance.…”
Section: Natural Compounds Regulate Obs and Ocs Autophagy Signaling P...mentioning
confidence: 99%